Gestão de desempenho na visão de Startups de RH: um estudo exploratório sobre tendências e valores em gestão de pessoas - Ferreira, Mariana Peixoto (2019)
The digitalization and intensification of business competitiveness in the last decades have caused changes in the management models of people in organizations, as well as in the strategies for engagement and performance of individuals in the Digital Age. Many organizations have revisited and even deconstructed their performance management models in order to gain greater connection to today's people management needs. That is the case of companies such as GE, Adobe, Microsoft, Unilever, among others, that have abolished their annual appraisal cycles. More recent studies and criticisms in the academic literature on performance management point to a shift in focus: evolving from a focus on evaluation methods and metrics to strategies on people's development for performance. In this context of transformation, new actors in the human resources market are observed: the HR Techs. Such startups are organizations oriented to test and develop innovative solutions and technology applied to human resources challenges. In this exploratory research, we sought to understand emerging trends in performance management and the values behind this transition, from the perspective of the HR Techs (HR Startups). The option to focus on startups relay to the fact that they operate under the premise of developing innovations and technology in the human resources field, and are, therefore, more sensitive, prone and connected to trends in people management. For this study ten representatives of Brazilian human resources startups were interviewed, in order to understand their perception of trends in performance management. The collection and analysis of data revolved around three aspects, in line with the general and specific objectives of this work, they are: the (1) elements of practices considered "traditional" by startups, (2) as opposed to the elements of the strategies perceived as emerging, and finally , (3) the central values that permeate this transition. The narratives of these interviews were analyzed using the content analysis method. The results of this research point out that, under the view of human resource startups, performance management models and strategies demand a more fluid and continuous format, where technology is widely applied to broaden feedbacks in all directions, not restricted to managers and it`s subordinates. Transparency and continuous feedback are non-negotiable elements in emerging models, and the main focus should be on the development of people and teams, not their evaluation. Such transitions will require leadership preparation and, above all, apply only to organizations that connect to a culture of continuous feedback and development, with trust and transparency. Finally, although technology can be helpful for the operationalization of continuous formats in performance management, regarding the capture, and analysis of data, the technology itself is only one tool in this transformation: the main changes happen by culture, leadership mentality and protagonism of individuals in its own development